The effect of surface treatment methods of tooth colored Restorations on shear bond strength - Mitra Tabari; Hengameh Safarcherati; Vahid Soltankarimi; Ali Bijani; Maryam Shojaee (Babol University of Medical Sciences, 2012)
Introduction: Due to undeniable effect of surface treatment on restoration bond strength, this study was conducted to measure and compare the shear bond strength of hybrid ionomer and compomer using the three different methods of surface conditioning. Methods: In this in vitro experimental study, 72 samples were prepared from hybrid ionomer (Vitremer-3M) and compomer (Compoglass-Vivadent) restoration materials on the basis of three methods of surface conditioning (etching with 37% phosphoric acid/using silicon carbide paper/micro abrasion with 50 μm aluminum oxide particles). After thermo cycling and simulating the oral environment, maximum shear bond strength of samples was measured by instron machine at a crosshead speed of 0.5 mm per minute on mega Pascal. The data were analyzed by SPSS software and ANOVA completely randomized design and two independent samples t-test. This significance level was considered p<0.05. Results: There was statistically significant difference between the shear bond strength of two types of restoration material, acid phosphoric and silicon carbide, after the different surface treatments (p=0.016 and p=0.002). In micro abrasion surface preparation method, no statistically significant difference was found in restoration shear bond strength. The shear bond strength of compomer group was also significantly more than hybrid ionomer group (p=0.015). Conclusions: Reconstruction capability of Compoglass was better than Vitremer.